MMCTS 2021
DOI: 10.1510/mmcts.2020.071
|View full text |Cite
|
Sign up to set email alerts
|

VATS parathyroidectomy for primary hyperparathyroidism

Abstract: Mediastinal ectopic parathyroid glands are uncommon. Traditionally, median sternotomies were performed to treat this type of lesion, resulting in a long, painful postoperative period and poor aesthetic results. With the advent of video-assisted thoracoscopic surgery, procedures were performed more frequently by this route with the same surgical and oncological results as those achieved with conventional surgery. The introduction of more sophisticated imaging studies, such as computed tomography, computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thoracoscopic parathyroidectomies, including those conducted through minimally invasive techniques, such as video-assisted thoracoscopic surgery (VATS), that are facilitated by having a precise preoperative location of the adenoma, have been safely used in selected adult cases of ectopic or extremely large orthotopic parathyroid tumors; the similar pediatric application also seems safe, according to current knowledge, despite a low level of statistical evidence [11,[80][81][82]. For example, Vitale et al [69] reported, in 2022, the first pediatric case of PHP-associated ectopic (intra-thymic) mediastinal adenoma complicated by bilateral slipped capital femoral epiphysis (the same team analyzed similar, previously published, cases and identified 13 reports with unilateral epiphysis lesions).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracoscopic parathyroidectomies, including those conducted through minimally invasive techniques, such as video-assisted thoracoscopic surgery (VATS), that are facilitated by having a precise preoperative location of the adenoma, have been safely used in selected adult cases of ectopic or extremely large orthotopic parathyroid tumors; the similar pediatric application also seems safe, according to current knowledge, despite a low level of statistical evidence [11,[80][81][82]. For example, Vitale et al [69] reported, in 2022, the first pediatric case of PHP-associated ectopic (intra-thymic) mediastinal adenoma complicated by bilateral slipped capital femoral epiphysis (the same team analyzed similar, previously published, cases and identified 13 reports with unilateral epiphysis lesions).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Case reports identified another seven subjects with the same postparathyroidectomy hypocalcemia-based syndrome; a potential connection with ectopic presentation or brown tumors was suggested, but there are limited data from a strictly statistical perspective [15,36,[69][70][71][72]74]. Minimally invasive thoracoscopic approaches seem safe, and they should be used for ectopic tumors when possible [11,[80][81][82].…”
Section: Trans-pandemic Insights Into Paediatric Phpmentioning
confidence: 99%